Measuring efficiency of practicum supervision at Sarawak teachers' training institute by using data envelopment analysis - Si, Tong Yong (2012)
The purpose of this study is to use Data Envelopment Analysis to measure the efficiency of practicum supervision of 20 units in Sarawak Teachers’ Training Institute. The inputs considered are the total number of lecturers Grade DG44; the total number of lecturers Grade DG48; and the total number of lecturers Grade DG52 as the supervisor for the trainees in each departments in Sarawak Teachers’ Training Institute and the outputs considered are the total number of trainees that are satisfied with the supervision of their supervisors on planning their teaching, the total number of trainees that are satisfied with the supervision of their supervisors on implementing their teaching, and the total number of trainees that are satisfied with the supervision of their supervisors on managing their classroom. Besides the overall performance model, six models are developed for the purpose of testing the sensitivity of the results, and hence identifying the strengths and weaknesses of the units. The findings show that eight units are technically-efficient. Among the efficient units, Special Education Unit, Malay Studies Unit and Moral Education Unit are the representative units. Data Envelopment Analysis helps in identifying the reference sets for the inefficient units and further determining the potential improvements. As such, it can be a valuable benchmarking tool for unit administrators.